Distance Basic Education in COVID-19 Time from the Analysis of the “Aprende en Casa” Strategy in Tlaxcala, México - Carro-Olvera, Adriana (2022)
Aim. This article aims to analyze the Aprende en casa [Learning from home] strategy designed by the Mexican Department of Education implemented in the State of Tlaxcala, México. Method. For this purpose, the study employed an exploratory, qualitative research design based upon the decoding of information, the identification of analysis categories, and the creation of factual and analytic matrixes. This study involved interviews with 28 sector heads and 210 supervisors held during the coordination of virtual meetings. Results. The main findings showed that most students participated in the Aprende en casa strategy. They also revealed that the students have poor use of information and communications technologies for learning; teachers and principals are in the same situation. This helped reach operative goals but not the substantive ones at the end of the 2019-2020 school year. WhatsApp was the most used tool to communicate the activities, thanks to the support of parents. Conclusions. The use of technology was not enough to bring learning to students. We have to transition from emergency remote teaching to more inclusive distance education.